The Infuence Of Using Android Education Application “Andre” To Adolescent’s Knowledge About Drug Abuse In Senior High School 8 Kediri - Sendra, Eny; Suwoyo, Suwoyo; Wijayanti, Lumastari Ajeng (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Android education application was a medium for health promotion to reduce the incidence of juvenile drug abuse. This study aims to analyze differences in knowledge of adolescents about drugs using the android education application at SMAN 8 Kota Kediri. The population in this study were all teenage boys and girls in class X in SMAN 8 Kota Kediri with a total of 350 students with a sample of 179 students, the sampling technique used Cluster Random Sampling. Data analysis using statistical tests WilcoxonMatch Pairt Test test results get a Zcount value of -11.409 (absolute value) with a significance of 0,000. Because Zcount has a significance of less than 0.050 (sig <0.050), Ho is rejected and H1 is accepted. so that it can be concluded that there is a significant effect on knowledge before and after being given an android education application